Millennium Development Goals (MDG) Gap Task Force Report 2008 - United Nations Department of Economic; Social Affairs (United Nations, 2008)
The present report was prepared by the MDG Gap Task Force which was created to improve the monitoring of the MDG 8 by leveraging inter-agency coordination. The objective of the report is to identify remaining obstacles to accelerate progress in the achieving the targets contained in MDG 8. It highlights the degree of compliance to the commitments made by developed and developing countries with a view to strengthening the global partnership for development. The main message of the report is that while there has been progress on several counts, important gaps remain in delivering on the global commitments in the area of aid, trade, debt relief, and access to new technologies and affordable essential medicines.